2016
DOI: 10.2460/ajvr.77.10.1101
|View full text |Cite
|
Sign up to set email alerts
|

Serum cholecystokinin concentrations in dogs with naturally acquired pituitary-dependent hyperadrenocorticism

Abstract: OBJECTIVE To determine serum cholecystokinin (CCK) concentrations in dogs with pituitary-dependent hyperadrenocorticism (PDH) and to evaluate associations among CCK concentration, PDH, and gallbladder mucocele (GBM). ANIMALS 14 client-owned dogs with PDH and 14 healthy dogs. PROCEDURES Dogs were separated into 4 groups: healthy dogs without gallbladder sludge (group A; n = 7), healthy dogs with gallbladder sludge (group B; 7), dogs with PDH and gallbladder sludge (group C; 8), and dogs with PDH and GBM (group … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 35 publications
1
5
1
Order By: Relevance
“…The significance of a reduction in CCK is important due to its role in gall bladder motility within the BT breed, although it is possibly relevant in other breeds presenting with GBM, despite non-BT not having a significant reduction in CCK in our study. Previous work has identified hyperadrenocorticism as an associative factor in GBM cases (Kim et al 2017), and dogs with hyperadrenocorticism have been shown to have a significant reduction in both CCK and leptin levels (Cho et al 2014, Noh et al 2016. Therefore, the finding of decreased CCK in dogs within this study and the previous identification of reduced CCK (and leptin) in dogs with hyperadrenocorticism suggest the cause of GBM in dogs with hyperadrenocorticism could also relate to gall bladder hypomotility.…”
Section: Discussionsupporting
confidence: 64%
See 3 more Smart Citations
“…The significance of a reduction in CCK is important due to its role in gall bladder motility within the BT breed, although it is possibly relevant in other breeds presenting with GBM, despite non-BT not having a significant reduction in CCK in our study. Previous work has identified hyperadrenocorticism as an associative factor in GBM cases (Kim et al 2017), and dogs with hyperadrenocorticism have been shown to have a significant reduction in both CCK and leptin levels (Cho et al 2014, Noh et al 2016. Therefore, the finding of decreased CCK in dogs within this study and the previous identification of reduced CCK (and leptin) in dogs with hyperadrenocorticism suggest the cause of GBM in dogs with hyperadrenocorticism could also relate to gall bladder hypomotility.…”
Section: Discussionsupporting
confidence: 64%
“…Additionally we ran CCK on these samples, without a known history of fat content of the food or exact timing of feeding, however all ELISAs were run on samples which were starved for a minimum of 8 hours. A previous study showed dogs with GBM had significantly higher pre-prandial CCK than control dogs (Noh et al 2016), and in humans lower basal CCK has been noted in patients with coeliac disease compared to controls (Thompson et al 1982). Therefore it seemed appropriate to use pre-prandial, basal samples in these dogs, and these results were deemed to be accurate for CCK measurement.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Serum or plasma cortisol concentrations in blood samples obtained before and after adrenocorticotropic hormone (ACTH) administration are commonly used for confirming a diagnosis of hyperadrenocorticism (HAC) or hypoadrenocorticism in dogs . Results of the ACTH stimulation test (ACTHst) are also used to aid in determining optimal dose and frequency of medications used in the short and long‐term management of dogs with HAC .…”
mentioning
confidence: 99%